Leukemic Reticulosis and Allied Disorders - Fukuda, Takao (The Tohoku Journal of Experimental Medicine, 1965)
The usage of the terms “leukemic reticulosis” and “leukemic reticulosar-comatosis” has been in confusion. They are applied to the cases with appearance of neoplastic reticulum cells in the peripheral blood. However, their implications, clinical, pathological and diagnostic, are indistinct and controversial. To define the concept of such conditions and pathological characteristics, the author investigated histological sections and blood films of 39 cases, which showed reticulum cells appearing in the peripheral blood. The following results were obtained: (1) Leukemic reticulosis is rapidly progressive and leads to the death of patients within four months. Histological features are characterized by diffuse medullary reticulosis of the lymph nodes and diffuse reticulum cell infiltration in various organs. (2) Leukemic reticulosarcomatosis is defined as hematogenous tumor cell dissemination of undifferentiated or reticular type reticulosarcoma at the terminal stage or as one of the results of chemotherapy or X-ray irradiation. (3) Even in Hodgkin disease-like granulomatous reticulosis, reticulum cells are observed in blood films. But these changes are regarded as cataplastic in nature. (4) In various reactive reticulosis, reticulum cells are observed in blood films. In association with various leukemias, reactive reticulosis exhibits malignant transition and neoplastic reticulum cells appear in peripheral blood at the terminal stage.